Elucidation of the tyrosinase/O2/monophenol ternary intermediate that dictates the monooxygenation mechanism in melanin biosynthesis - Kipouros, Ioannis; Stańczak, Agnieszka; Ginsbach, Jake W; Andrikopoulos, Prokopis C; Rulíšek, Lubomír; Solomon, Edward I (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Melanins are highly conjugated biopolymer pigments that provide photoprotection in a wide array of organisms, from bacteria to humans. The rate-limiting step in melanin biosynthesis, which is the ortho-hydroxylation of the amino acid L-tyrosine to L-DOPA, is catalyzed by the ubiquitous enzyme tyrosinase (Ty). Ty contains a coupled binuclear copper active site that binds O2 to form a μ:η2:η2-peroxide dicopper(II) intermediate (oxy-Ty), capable of performing the regioselective monooxygenation of para-substituted monophenols to catechols. The mechanism of this critical monooxygenation reaction remains poorly understood despite extensive efforts. In this study, we have employed a combination of spectroscopic, kinetic, and computational methods to trap and characterize the elusive catalytic ternary intermediate (Ty/O2/monophenol) under single-turnover conditions and obtain molecular-level mechanistic insights into its monooxygenation reactivity. Our experimental results, coupled with quantum-mechanics/molecular-mechanics calculations, reveal that the monophenol substrate docks in the active-site pocket of oxy-Ty fully protonated, without coordination to a copper or cleavage of the μ:η2:η2-peroxide O-O bond. Formation of this ternary intermediate involves the displacement of active-site water molecules by the substrate and replacement of their H bonds to the μ:η2:η2-peroxide by a single H bond from the substrate hydroxyl group. This H-bonding interaction in the ternary intermediate enables the unprecedented monooxygenation mechanism, where the μ-η2:η2-peroxide O-O bond is cleaved to accept the phenolic proton, followed by substrate phenolate coordination to a copper site concomitant with its aromatic ortho-hydroxylation by the nonprotonated μ-oxo. This study provides insights into O2 activation and reactivity by coupled binuclear copper active sites with fundamental implications in biocatalysis.
Keywords: Peroxides; Catalysis; Monophenol Monooxygenase; monooxygenase; vazebná místa; tyrosinasa; katalýza; melanin biosynthesis; bakteriální proteiny; peroxidy; fenoly; Phenols; Bacterial Proteins; melaniny; Melanins; binuclear copper; měď; Copper; Oxygen; tyrosinase; Streptomyces; oxygen activation; kyslík; Binding Sites